(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aimed to determine the implementation of the Population Administration Information System (SIAK) policy in electronic-based population services at the Civil Registry Office of Palopo City based on indicators of communication, resources, attitudes/dispositions, and bureaucratic structure. This study used a qualitative descriptive type of research, to provide an overview of the population administration information system (SIAK). The data analysis technique used data reduction, data presentation and conclusion . Then the data collection techniques used observation, interviews and documentation. The results of the study indicated that (a) communication between the head of the service and the employees (i) had been going well in terms of carrying out the duties and responsibilities given and carried out in accordance with the applicable rules; (b) the resources, tools/or facilities were sufficient but only needed to improve what was not yet available; (c) attitude/disposition, the community in accessing the system easily because of the friendly attitude built by employees; (d) bureaucratic structure, a stipulation in responding to an employee who worked, a provision that was applied by the service.